Sound-Strength Driven Parametric Design of an Acoustic Shell in a Free Field Environment. Issue 1 (March 2014) - Palma, Marco; Sarotto, Maddalena; Echenagucia, Tomás Méndez; Sassone, Mario; Astolfi, Arianna
Focusing on the issues of sound propagation in a free field condition and on the concept of uniform sound energy in an outdoor performance environment, our research aimed to develop a computer-aided process for the generation of reflective acoustic surfaces to be used as concert-shells, a computational design tool for acoustic form-finding. The project is ultimately aimed to investigate the acoustic potential of complex and doubly-curved surfaces through the analysis of the Total Relative Sound Level / Strength parameter (G), with reference to the proposed values set by M. Barron, based upon the source-receiver distance and the subsequent subjective judgments on loudness. A simplified and fast ray-tracing acoustic simulation algorithm was developed in combination with parametrically controlled shape variations of the reflective surfaces. Sound energy uniformity evaluation function considering the direct and reflected sound components was written in order to define and evaluate the rate of distribution uniformity of sonic energy over an audience. This evaluation function was used in a genetic algorithm that enabled us to explore a wide set of surface morphologies which allowed us to isolate the fittest one to our specific uniformity requirements. At the end of the genetic search, an acoustic simulation plug-in called Pachyderm was employed with both NURBS and mesh-based acoustic simulations in order to validate the genetically selected surfaces with specific reference to G values. A further step of resultant data visualization and human selection was necessary to compare the output data and to evaluate the final surfaces from an architectural perspective.